THE IMPACT OF CASE LAW TO THE AMENDMENTS TO THE LAW ON CIVIL LIABILITY FOR DEFAMATION AND INSULT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The legal system in Republic of North Macedonia being a continental or romano-germanic legal system places the main emphasis on a set of core principles that are codified into a single referable system serving as a primary source of law. Unlike the common law legal systems that are primarily based on judicial proceedings, using a case law as source of law or at least a reference has never been a common practice in the Macedonian law-making process or application of law in court cases. However, the Law on Civil Liability on Defamation and Insult installed an open gate for the jurisprudence of the European Court of Human Rights giving the Macedonian judges a possibility to evoke and to ground its decision according to the relevant ECHR case law.Moreover, the Macedonian national courts built solid corpus of national decisions on defamation and offence. This paper will demonstrate the impact such decisions had on the latest amendments to the Law on Civil Liability on Defamation and Insult, and it will demonstrate the corrective power the judicial decision has when the judges apply the law. For the purpose of methodological precision, the selected case law for this study is based on 30 decisions form the geographical coverage of all the four appellate courts in North Macedonia and over 15 primary courts.
Keywords: defamation, insult, law, case law, impact